FUNCTIONAL POTENTIAL OF PROSOPIS AFRICANA WHOLE FRUIT: INSIGHTS INTO ANTIOXIDANT, ANTIDIABETIC, AND IMMUNOMODULATING ACTIVITIES - Salawu, Kayode; Balogun , Quadri Olayinka; Salawu, Oluwatoyosi Olatoun; Aamer, Muhammad; Shehla, Nuzhat; Wang, Yan; Adegboye, Olutosin Alarape (FUDMA JOURNAL OF SCIENCES, 2025)
The global rise in chronic conditions such as diabetes, immune dysfunction, and oxidative stress-related disorders has intensified the search for multifunctional plant-based remedies. This study evaluated the antioxidant, α-glucosidase inhibitory, and immunomodulatory properties of the whole fruit extract and fractions of Prosopis africana. Whole fruits were extracted with 70% methanol and fractionated into hexane (PAF-1), dichloromethane (PAF-2), ethyl acetate (PAF-3), and aqueous (PAF-4) components. Antioxidant activity was assessed via DPPH radical scavenging. α-Glucosidase inhibition was analysed through enzyme kinetics using acarbose as a standard. Immunomodulatory effects were evaluated by measuring ROS inhibition in stimulated human peripheral blood mononuclear cells (PBMCs). All extracts exhibited dose-dependent antioxidant activity. PAF-1 and PAF-2 demonstrated strong radical scavenging capacities with IC₅₀ values of 0.23±0.02 and 0.259±0.01 µg/mL, respectively, significantly lower than gallic acid (22.1±1.85 µg/mL). PAF-1 showed the most potent α-glucosidase inhibition (IC₅₀ = 44.83±1.09 µg/mL), surpassing acarbose (IC₅₀ = 377.75±1.34 µg/mL), while PAF-2 showed the highest ROS inhibition (44.7%) in PBMCs, although lower than ibuprofen (73.2%). P. africana whole fruit exhibits significant multifunctional bioactivities, validating traditional claims and highlighting its potential as a source of nutraceutical or phytopharmaceutical agents for managing chronic diseases.
Keywords: Prosopis africana; antioxidant; a-glucosidase Inhibition; ROS; Immunomodulation; immunomodulation, plant-based therapy